Analysis of the Development of Preschool Children with Autism Spectrum Disorder: A Qualitative Descriptive Study - Aini, Irma Soraya Nur; Wahyuni, Endang Sri; Hastuti, Roh (Poltekkes Kemenkes Surakarta, 2023)
Background: Preschool is an important period in child development because of the acceleration in motor, language, and social-emotional skills. Children with Autism Spectrum Disorder (ASD) have difficulties in social, communication, and repetitive behavior aspects that impact developmental delays. This study aims to analyze the developmental aspects of preschool-aged children with ASD. Methods: This study used a descriptive qualitative approach. The sample consisted of four preschool-aged children with ASD and their four mothers, who were selected using purposive sampling based on the Denver II criteria. Data collection was conducted through interviews and observations of child development during one assessment period. Data analysis was performed thematically with triangulation of sources and techniques and verification through member checks to ensure data validity. Results: The thematic analysis yielded three main themes, namely: (1) motor aspects, which include delays in locomotor skills, manipulative movements, eye-hand coordination, and early writing skills; (2) language aspects showing barriers in speech initiation and language expression abilities; and (3) socio-emotional aspects including delays in environmental exploration, independence, and social interaction abilities. Conclusion: Preschool-aged children with ASD have developmental delays in motor, language, and social-emotional aspects with varying degrees of severity according to age. Structured occupational therapy and early intervention based on multisensory stimulation are recommended to support the optimal developmental achievement of children with ASD.